Свадьба по всем правилам и на любой вкус: сборник / О. Веселовская - Веселовская Ольга (АСТ, 2002)
Экземпляры: ЧЗ (20150907) / Инвентарный номер: 37152 / Цена: 52 / Авт.знак: В 38 / ГРНТИ: 03 / ББК: 63.5